Aplicação do framework ágil Scrum para projetos de Bpms no contexto da transformação digital do Sebrae/PB - Silva, Douglas Demingos Cavalcanti P da (2023)
At the same time, innovations in technology have driven intense disruption, mainly as a result of a conversion movement called Digital Transformation. However, the Covid- 19 pandemic emerged as a powerful catalyst for this movement, as it began to require a quick reaction from organizations to the new demands of the emerging scenario. To this end, as a mechanism for achieving the intended transformations, organizations have replaced their software development processes, based on traditional management methods, by frameworks based on agile theories, due to their flexible and dynamic structures, which favor inspections and adaptations in the course of carrying out the projects. In that context, this paper aims to present a case study on the application of Scrum theory to the development of a new BPMS (Business Process Management System) software increment, which aimed to automate hiring processes of a non-profit entity in the Sistema S, the Sebrae Paraíba. The study presented a reference model for the adoption of agile practices in development routines, especially showing which ones were successfully applied, such as artifacts, roles and iterations of Sprints containers. The method chosen for data collection was direct observation and data extraction from the datasets of the tools used to support the agile framework. It was concluded that the results, from quantitative and qualitative analysis of data, suggested the successful application of the model, due to the achievement of better internal communication, increased compliance, reduction of time, risk control and increased performance of the team. Also noteworthy is the greater final quality measured by the software, despite the effective use of constant monitoring and guidance towards the agreed goals and deadlines, factors that made it possible to surpass the overall performance of the project.